Integrando o conteúdo de MCU e MHS por meio de observação as luas de Júpiter - (:unkn) unknown (Universidade Federal do Pampa, 2018)
In this thesis, we present a work proposal to integrate the concepts of Uniform Circular Movement and Simple Harmonic Movement with some observations on the moons of Jupiter. This research was conducted with the 2nd Grade students from Instituto Federal Farroupilha – Alegrete in 2017. More specifically, we investigate the significant learning which is based on Constructivist approach. It gives us a series of arguments on knowledge construction as the didactic material has to be meaningful to the students. This way, we propose a sequence of activities based in the Potentially Meaningful Teaching Units (PMTU), aiming to bring a material that is really significant and raise the students’ interest in science. We made several activities such as computer simulations, observations on the moons of Jupiter, and modeling the motions of the moons through observations notes. In the data analysis, it was applied rubrics from a qualitative viewpoint as well as pretest and posttest activities in the experimental research, assessing with the Student’s t- test. The results show us that that sequence was successful in relation to significant learning, showing that the students improved in knowledge construction after the activities.
Keywords: UEPS; Luas de Júpiter; MCU; MHS; PMTU; Moons of Jupiter; CNPQ::CIENCIAS EXATAS E DA TERRA